2020
DOI: 10.1080/02673843.2020.1758174
|View full text |Cite
|
Sign up to set email alerts
|

The attitude towards E-cigarettes, disengagement belief, E-cigarette health literacy and susceptibility among youths and adolescents

Abstract: Purpose: The marketing effort of e-cigarettes producers makes youths and adolescents less alert about the potential harm of e-cigarettes. The trend of e-cigarette use among vocational school students becomes increasingly severe in China. This study is to reveal the psychological process that plays a critical role in affecting students' e-cigarette susceptibility. Method: This study uses the time-lagged data collected from 835 vocational school students in China and the structural equation modelling.Findings: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
6
1
1
Order By: Relevance
“…Therefore, contrary to the findings of this study, more American youths were found to have a negative attitude towards e-cigarettes by perceiving it as harmless and popular. 29 Many respondents in this study were unlikely to use e-cigarettes when offered by friends contrary to the favourable disposition exhibited by undergraduate students towards e-cigarettes in a study conducted in Saudi Arabia. 30 Some respondents in this study reported that they would not enjoy using e-cigarettes, with about 42.62% stating that they were unlikely to use e-cigarettes in the next 12 months.…”
Section: Discussioncontrasting
confidence: 66%
“…Therefore, contrary to the findings of this study, more American youths were found to have a negative attitude towards e-cigarettes by perceiving it as harmless and popular. 29 Many respondents in this study were unlikely to use e-cigarettes when offered by friends contrary to the favourable disposition exhibited by undergraduate students towards e-cigarettes in a study conducted in Saudi Arabia. 30 Some respondents in this study reported that they would not enjoy using e-cigarettes, with about 42.62% stating that they were unlikely to use e-cigarettes in the next 12 months.…”
Section: Discussioncontrasting
confidence: 66%
“…Children have weak resilience, social and structural fragility in the face of health stress, and often need social and family support ( Li et al, 2020b , Qi and Wu, 2020 , Yuan and Li, 2020 ). But the socio-economically disadvantaged status of families of origin exhausts material, emotional and social resources of parents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Characteristics of the included studies are summarized in the Supplementary file. The 66 included articles included 23 articles from America 19,20,39,42,[43][44][45]52,53,[60][61][62][73][74][75][76]82,83,85,[93][94][95]98 , five from Iran 18,77,78,80,81 , five from Denmark 37,54,55,66,87 , four from Japan 58,84,86,88 , three from Turkey 48,96,97 , three from the Netherlands 56,63,89 , three from China [70][71][72] , three from Australia 38,59,64 , two from Taiwan 51,…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%